The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1039/c9sc00334g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sterically hindered 4,5-diarylphenanthrenes via acid-catalyzed bisannulation of benzenediacetaldehydes with alkynes

Abstract: Acid-catalyzed bisannulation of benzenediacetaldehydes with alkynes provided a rapid access to sterically hindered 4,5-diarylphenanthrenes and multisubstituted phenanthrenes regioselectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This demonstrated that the half-life of racemization (in toluene at 85 °C) is 24 h, and the racemization barrier was determined to be 31.0 kcal/mol at 298 K (Figures S13 and S14), which is in good agreement with the DFT calculations. Furthermore, the barrier for the helical inversion of 3c is remarkably high compared to 4,5-diphenylphenanthrene ( 1 ) (Δ G ⧧ = 22.1 kcal/mol, Figure S7), which is in line with reports that 4,5-bis­(4-ethylphenyl)­phenanthrene racemizes fairly rapidly in the solution above 50 °C . These results demonstrate that the twisted structure can enhance the axial chirality of the 4,5-diphenylphenanthrene subunit to create a shape-persistent macrocycle.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This demonstrated that the half-life of racemization (in toluene at 85 °C) is 24 h, and the racemization barrier was determined to be 31.0 kcal/mol at 298 K (Figures S13 and S14), which is in good agreement with the DFT calculations. Furthermore, the barrier for the helical inversion of 3c is remarkably high compared to 4,5-diphenylphenanthrene ( 1 ) (Δ G ⧧ = 22.1 kcal/mol, Figure S7), which is in line with reports that 4,5-bis­(4-ethylphenyl)­phenanthrene racemizes fairly rapidly in the solution above 50 °C . These results demonstrate that the twisted structure can enhance the axial chirality of the 4,5-diphenylphenanthrene subunit to create a shape-persistent macrocycle.…”
Section: Resultssupporting
confidence: 87%
“…These successful materials applications have encouraged us to develop a new 3D scaffold to widen the scope of available building blocks and introduce new properties to the resulting new topological molecular nanocarbons. Recently, our group has described a one-step synthesis of helical 4,5-diarylphenanthrene by acid-catalyzed bisannulation of 1,4-benzenediacetaldehyde with aryl alkynes . Due to the steric hindrance caused by the 4,5-diphenyl substitution in 4,5-diphenylphenanthrene, its derivatives are ideal candidates to be used as chiral nonplanar building blocks for the synthesis of novel 3D π-conjugated aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…1 was therefore disconnected into the highly twisted 4,5‐di‐ o ‐tolylphenanthrene 6 , which contains the complete inner edge of the helicene (Scheme 1). 6 is accessible via a double electrophilic benzannulation involving 1‐ethynyl‐2‐methylbenzene 4 and dialdehyde 5 , as recently reported by Itami and co‐workers [45,46] . Compound 6 was subjected to radical bromination and subsequent hydrolysis, to yield the key dialdehyde 7 , which formed as a mixture of atropisomers.…”
Section: Resultsmentioning
confidence: 63%
“…6 is accessible via a double electrophilic benzannulation involving 1-ethynyl-2-meth-ylbenzene 4 and dialdehyde 5, as recently reported by Itami and co-workers. [45,46] Compound 6 was subjected to radical bromination and subsequent hydrolysis, to yield the key dialdehyde 7, which formed as a mixture of atropisomers. This mixture underwent Grignard addition with mesitylmagnesium bromide, followed by Lewis acid-catalyzed cyclization, to provide the dihydrodinor [7]helicene 8.…”
Section: Resultsmentioning
confidence: 99%
“…Phenanthrene structures are also synthesized from biphenyls; for example, the acid-catalyzed intramolecular cyclization of 2-alkynyl biphenyl (iii) 25 , 26 , cross-coupling reactions of 2-halogenated biphenyl with alkynes (iv) 27 29 , and ring-closing metathesis of 2,2’-vinyl biphenyls (v) 30 , 31 . Itami et al have developed various sophisticated molecular transformation methodologies for the synthesis of different π-aromatics, including phenanthrene derivatives 32 , based on transition-metal-catalyzed coupling and subsequent annulation reactions 33 , 34 . However, previously reported synthetic methodologies require stoichiometric amounts of oxidants and/or homogeneous metal catalysts; therefore, the risk of contamination of inorganic residues derived from catalysts and/or substrates into products is an issue that should be addressed to achieve super-high-purity organic electronic materials with excellent performance 35 37 .…”
Section: Introductionmentioning
confidence: 99%